(untitled) (Research, Society and Development, 2020)
This work presents the results of a research that sought to investigate what has been published in the last ten years on teacher training for the initial years and on the Problem-Based Learning Methodology. The methodology of this study is of a qualitative nature and the analysis of the data obtained was performed through the method of Discursive Textual Analysis. The investigation was carried out in the Digital Library of Theses and Dissertations, in the Capes Periodicals and in the Online Electronic Scientific Library (Scielo). The search resulted in a total of one hundred and eighty-five (185) publications, of which six (06) publications related to the researched theme, that is, they presented the two criteria selected for the search. The results allow us to infer that most publications are related to the discipline of mathematics; and used definitions such as “problem-solving”, “problem-solvin” and “problem-solving”. Such results may be related to the fact that this methodology is little known in Brazil, or is still commonly used in exact disciplines.